A exposição materna e da prole à dieta de cafeteria promove alterações morfológicas tecido específicas - Santos, Carolyne Doneda Silva (2016)
We, herein, evaluated whether the exposure of rats to a cafeteria diet pre-and/or post-weaning, alters histological characteristics in the White Adipose Tissue (WAT), Brown Adipose Tissue (BAT), and liver of young adult male offspring. Female Wistar rats were divided into Control (CTL; rats fed on standard rodent chow) and Cafeteria (CAF; fed on cafeteria diet during their entire life). After birth, male offspring only (F1) were divided into four groups (8 pups/dams) and received the CTL or CAF diet during their entire lives: CTL-CTLF1, control offspring born from dams that were fed on control diet; CTL-CAF F1, cafeteria offspring born from dams that were fed on control diet; CAF-CTL F1, control offspring born from dams that were fed on a cafeteria diet; CAF-CAF F1, cafeteria offspring born from dams that were fed on a cafeteria diet. Biometrics, metabolic parameters, and liver, BAT and WAT histology were assessed. Data obtained were integrated using the Principal Component Analysis (PCA). PCA showed that maternal CAF diet protects offspring from the deleterious effects provoked by the exposure to an obesogenic diet during adult life, as demonstrated by the absence of alteration in body weight and fat accumulation, but failed to protect BAT and liver, suggesting that the impact of maternal CAF diet is tissue-specific.